Better survival in right-sided versus left-sided stage I - III colon cancer patients. Issue 1 (December 2016) - Warschkow, Rene; Sulz, Michael; Marti, Lukas; Tarantino, Ignazio; Schmied, Bruno; Cerny, Thomas; Güller, Ulrich
Abstract Background The distinction between right-sided and left-sided colon cancer has recently received considerable attention due to differences regarding underlying genetic mutations. There is an ongoing debate if right- versus left-sided tumor location itself represents an independent prognostic factor. We aimed to investigate this question by using propensity score matching. Methods Patients with resected, stage I - III colon cancer were identified from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2012). Both univariable and multivariable Cox regression as well as propensity score matching were used. Results Overall, 91, 416 patients (51, 937 [56.8 %] with right-sided, 39, 479 [43.2 %] with left-sided colon cancer; median follow-up 38 months) were eligible. In univariable analysis, patients with right-sided cancer had worse overall (hazard ratio [HR] = 1.32, 95 % CI:1.29–1.36, P < 0.001) and cancer-specific survival (HR = 1.26, 95 % CI:1.21–1.30, P < 0.001) compared to patients with left-sided cancer. After propensity score matching, the prognosis of right-sided carcinomas was better regarding overall (HR = 0.92, 95 % CI: 0.89 − 0.94, P < 0.001) and cancer-specific survival (HR = 0.90, 95 % CI:0.87 − 0.93, P < 0.001). In stage I and II, the prognosis of right-sided cancer was better for overall (HR = 0.89, 95 % CI:0.84–0.94 and HR = 0.85, 95 % CI:0.81–0.89) and cancer-specific survival (HR = 0.71, 95 % CI:0.64 − 0.79 and HR = 0.75, 95 % CI:0.70–0.80). Right- and left-sided colon cancer had a similar prognosis for stage III (overall: HR = 0.99, 95 % CI:0.95–1.03 and cancer-specific: HR = 1.04, 95 % CI:0.99–1.09). Conclusions This population-based analysis on stage I - III colon cancer provides evidence that the prognosis of localized right-sided colon cancer is better compared to left-sided colon cancer. This questions the paradigm from previous research claiming a worse survival in right-sided colon cancer patients.